Phenytoin-induced DRESS syndrome: A multidisciplinary case study in precision medicine and advanced therapeutics - Pratama, Frida Kurnia; Hikmah, Zahrah; Ervianti, Evy; Gunawan, Prastiya Indra; Hartanto, Felix; Putra, Azwin Mengindra; Endaryanto, Anang (Edelweiss Applied Science and Technology, 2024)
This case report aims to examine the diagnostic and therapeutic approach for phenytoin-induced Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome in a pediatric patient, emphasizing the importance of early recognition and intervention. A 17-year-old male presented with a pruritic rash, fever, lymphadenopathy, and elevated liver enzymes one month after starting phenytoin for epilepsy. Diagnosis was confirmed using the RegiSCAR scoring system, which objectively assessed clinical and laboratory findings. The patient received high-dose corticosteroids and N-acetylcysteine (NAC) after discontinuing phenytoin, with regular monitoring of clinical and laboratory parameters. Timely withdrawal of phenytoin, along with corticosteroid and NAC therapy, led to the resolution of symptoms without long-term complications. The RegiSCAR scoring system proved invaluable for accurate and swift diagnosis, supporting its utility in pediatric DRESS cases. This case also suggests the potential of genetic screening, particularly HLA typing, for identifying high-risk individuals, although it was not utilized here. Early diagnosis and multidisciplinary management are critical for favorable outcomes in pediatric DRESS cases. Routine HLA screening could help prevent DRESS syndrome in patients prescribed high-risk medications, though further studies are needed to assess feasibility and cost-effectiveness. This case underlines the value of standardized treatment protocols and personalized medicine in managing drug hypersensitivity reactions effectively.